Plant communities as a tool in temporary ponds conservation in SW Portugal - C. Pinto-Cruz, J. A. Molina (2009)
Temporary ponds are seasonal wetlands annually subjected to extreme and unstable ecological conditions, neither truly aquatic nor truly terrestrial. This habitat and its flora have been poorly studied and documented because of the ephemeral character of the flora, the changeable annual weather that has a great effect on the small, herbaceous taxa and the declining abundance of temporary ponds. The objectives of this study are: (a)to define plant community diversity in terms of floristic composition of ephemeral wetlands in SW Portugal, (b) to identify temporary pond types according to their vegetation composition and (c) to identify those ponds that configure the European community priority habitat (3170* – Mediterranean temporary ponds). Vegetation sampling was conducted in 29 ponds, identifying 168 species grouped among 15 plant communities. Soil texture, pH, organic C and N content were measured, but only N and percent of clay appear to be related with the distribution of each community type. The results showed that ephemeral wetlands could be classified into four type: vernal pools, marshlands, deep ponds and disturbed wetlands. Vernal pools correspond to the Mediterranean temporary ponds (3170*), protected as priority hab- itat under the EU Habitats Directive. Submersed Isoetes species (Isoetes setaceum and Isoetes velatum) represents, together with Eryngium corniculatum, the indicator species for vernal pools. We identify also indicator plant communities of this priority habitat, namely I. setaceum and E. corniculatum–Baldellia ranunculoides plant communities. In this region, the conservation of temporary ponds has so far been compatible with traditional agricultural activities, but today these ponds are endangered by the intensification of agriculture and the loss of traditional land use practices and by the development of tourism.